Briefing: Specific gravity of solids relationship with ignition loss for peaty soils. Issue 3 (15th July 2020) - Li, Weichao; O'Kelly, Brendan C; Yang, Min; Fang, Kunbin; Li, Xuemei; Li, Hui
Abstract : Peaty soils have an extremely high water content and a low specific gravity of solids ( G s ) compared with most inorganic soils. Accurate knowledge of the G s value allows void ratio computations for given water contents and densities. However, G s determinations using the standard pycnometer test are time consuming and pernickety, such that the G s value is often predicted by way of ignition loss ( N ) correlations instead. This paper presents original G s – N data for 25 peaty soils ( N = 23–86%) from the Dian-Chi Lake area, Kunming City, China, along with a data set assembled from various sources in the literature for 77 peaty clays and peats. The main research aim is to investigate correlations between G s, natural water content ( w n ) and N for the standard ignition temperature of 440°C, thereby allowing indirect G s estimations. For the 102 peaty soils examined, the best-fit G s – N correlation was obtained for specific gravities of the inorganic and organic solids fraction values of 2.77 and 1.35, respectively. A weaker inverse bilinear relationship was found between G s and w n . To overcome procedural differences between codes and for previous experimental work, it is recommended that an oven temperature of 105°C be consistently used for drying peaty soil specimens.